The Effect Of Characteristics Of Individual, Self Leadership, Commitment To Profession On Performance Of Lecturer's In The High Protection Of Kopertis Private East Java VII Region - Enni Sustiyatik; Ahmad Ridwan; Anton Respati Pamungkas; Abdul Kadir (Common Publisher, 2019)
This study aims to analyze the influence of individual characteristics, self-leadership, commitment to the profession on the performance of lecturers at private universities Kopertis Region VII East Java. The method used in this study is the survey method conducted on lecturers S1 Studies Program PTS Management. In Kopertis VII, which totaled 1457 people. With the consideration of lecturers have understood and actively carry out Tri Dharma Perguruan Tinggi. The sample in this research is 400 respondents. The data used in this study is the primary data sourced from the questionnaire. Data analysis and hypothesis test in this research using Structural Equation Model (SEM). The results showed that each variable of individual characteristics, self leadership, commitment to the profession have a significant effect on the performance of lecturers at private universities Kopertis Region VII East Java.